Shelf-life extension of traditional licorice root “sherbet” with a novel pulsed electric field processing - Akdemir Evrendilek, Gulsun; Tanriverdi, Hakan; Demir, Irem; Uzuner, Sibel (Frontiers in Food Science and Technology, 2023)
Pulsed electric fields (PEF) processing of licorice root “sherbet” (LRS) by various electric field strengths (7.00, 15.50 and 24.10 kV/cm), treatment times (108, 432 and 756 sec) and processing temperatures (6, 18 and 30 °C) according to Box-Behnken design were performed. The samples were analyzed for pH, titratable acidity, conductivity, turbidity, total reducing sugar, color (L*, a*, b*), hue, chroma, total color difference, color intensity, color tone, yellow, red and blue color tones, total antioxidant capacity, total phenolic substance content and sensory properties. Results revealed that PEF processing did not adversely affect most of the physical, chemical and sensory properties of LRS with maximum 2.48, 4.04, 1.78 and 1.20 log reductions on the initial total mesophilic aerobic bacteria, total mold and yeast, Bacillus circulans and Candida tropicalis. The response variable modeled for the PEF was found to be conductivity with the optimum processing conditions of 6.90 kV/cm, 756.00 µs and 7.48 °C. After that, the samples were stored at 4 and 22 °C for the shelf-life studies. Control samples at 4 and 22 °C were spoiled at the 5th and 2nd days; whereas PEF treated samples stored at 4 °C began to deteriorate after 40th day and the samples stored at 22 °C after the 30th day, respectively. It was revealed that PEF is suitable process to extend shelf-life of licorice “sherbet” with preservation of physicochemical and sensory properties.